Manipulation of Spray-Drying Conditions to Develop an Inhalable Ivermectin Dry Powder - Tushar Saha; Shubhra Sinha; Rhodri Harfoot; Miguel E. Quiñones-Mateu; Shyamal C. Das (MDPI AG, 2022)
SARS-CoV-2, the causative agent of COVID-19, predominantly affects the respiratory tract. As a consequence, it seems intuitive to develop antiviral agents capable of targeting the virus right on its main anatomical site of replication. Ivermectin, a U.S. FDA-approved anti-parasitic drug, was originally shown to inhibit SARS-CoV-2 replication in vitro, albeit at relatively high concentrations, which is difficult to achieve in the lung. In this study, we tested the spray-drying conditions to develop an inhalable dry powder formulation that could ensure sufficient antiviral drug concentrations, which are difficult to achieve in the lungs based on the oral dosage used in clinical trials. Here, by using ivermectin as a proof-of-concept, we evaluated spray-drying conditions that could lead to the development of antivirals in an inhalable dry powder formulation, which could then be used to ensure sufficient drug concentrations in the lung. Thus, we used ivermectin in proof-of-principle experiments to evaluate our system, including physical characterization and in vitro aerosolization of prepared dry powder. The ivermectin dry powder was prepared with a mini spray-dryer (Buchi B-290), using a 23 factorial design and manipulating spray-drying conditions such as feed concentration (0.2% w/v and 0.8% w/v), inlet temperature (80 °C and 100 °C) and presence/absence of L-leucine (0% and 10%). The prepared dry powder was in the size range of 1-5 μm and amorphous in nature with wrinkle morphology. We observed a higher fine particle fraction (82.5 ± 1.4%) in high feed concentration (0.8% w/v), high inlet temperature (100 °C) and the presence of L-leucine (10% w/w). The stability study conducted for 28 days confirmed that the spray-dried powder was stable at 25 ± 2 °C/<15% RH and 25 ± 2 °C/ 53% RH. Interestingly, the ivermectin dry powder formulation inhibited SARS-CoV-2 replication in vitro with a potency similar to ivermectin solution (EC50 values of 15.8 µM and 14.1 µM, respectively), with a comparable cell toxicity profile in Calu-3 cells. In summary, we were able to manipulate the spray-drying conditions to develop an effective ivermectin inhalable dry powder. Ongoing studies based on this system will allow the development of novel formulations based on single or combinations of drugs that could be used to inhibit SARS-CoV-2 replication in the respiratory tract.